A numerical CFD investigation of sand screen erosion in gas wells: Effect of fine content and particle size distribution - Abduljabbar, A. (Elsevier B.V., 2021)
Sand screen is frequently used as a sand control device in oil and gas wells to prevent or minimize sand production. However, the sand screen may undergo mechanical erosion due to continuous impingement and passage of sand particles through its apertures. In addition, the design of most sand screensâ spacing allows fine particles <44 Î¼m to pass through. According to previous studies, the existence of fines can also lead to erosion failures. In this study, the Eulerian-Lagrangian approach of dense discrete phase model (DDPM) has been used and evaluated for computational fluid dynamics (CFD) based erosion modelling of sand screen erosion because of the entrainment of fine particles in gas flow. Two sand types having different particle size distributions (PSD) and fine concentrations were studied. For the CFD erosion simulation, four erosion models were used, and then the effect of PSD of fines-inclusive sand particles on erosion magnitude has been investigated. The CFD simulation results were validated against the output of a reliable experimental-based correlation. Erosion results using McLaury model showed the least error and good agreement compared to the other models. For the two investigated sand types, using PSD for erosion prediction using CFD resulted in a higher value of maximum erosion when compared with the constant size simulation results. The value of the maximum erosion has increased 105.9 from the constant size results for sand type-I and 82.5 for sand type-II. The paper presents the first-ever comprehensive analysis study of its kind about the effect of fines-inclusive sand on the erosion of sand screen, considering the particle size distribution (PSD). The results of this study revealed the importance of considering erosion caused by fines, especially at high flow velocities. Â© 2021 Elsevier B.V.